A comparative study of early and late onset freezing of gait in Parkinson's disease - Shweta Prasad; Abhishek Lenka; Albert Stezin; Rajini M Naduthota; Menka Jha; Ravi Yadav; Pramod Kumar Pal (Annals of Indian Academy of Neurology, 2018)
Background: Freezing of gait (FOG) is a common and debilitating symptom in Parkinson's disease (PD); the pathogenesis and natural course of which has not been fully understood. Objectives: This study was performed to evaluate patients with FOG in PD and ascertain factors contributing to an early onset of FOG in patients with PD. Methodology: A chart review of 100 patients with PD (FOG [+] 50, FOG [−]: 50) was performed. FOG (+) patients were subdivided by a median split of time from motor onset to development of FOG (median: 6 years) into early onset FOG (EOFOG [n = 24]) and late onset FOG (n = 26). Results: The FOG (+) group had a significantly longer duration of motor symptoms, a higher Hoehn and Yahr stage, and greater severity of disease. Festination, falls, and wearing off were more prevalent in the FOG (+) group. Several nonmotor symptoms (NMS) such as constipation, psychosis, fatigue, weight loss, drooling, excessive sweating, depression, and postural giddiness were significantly higher in the FOG (+) group. The EOFOG group had a later age at onset of motor symptoms. There were no significant differences observed in the NMS, with the exception of fatigue in EOFOG. Conclusions: FOG is associated with longer disease duration and higher severity of disease. FOG (+) patients have distinct NMS which are contributory to disease morbidity. EOFOG might be associated with an accelerated disease progression and is linked with older patients and shorter disease duration.